Temperature-dependent small RNA expression in Drosophila melanogaster. Issue 3 (4th March 2018) - Fast, Isabel; Rosenkranz, David
ABSTRACT: Temperature has a major impact on gene expression in ectotherms. But until recently, it was not clear in which way, if any, small non-coding RNAs such as miRNAs or piRNAs contribute to thermosensitive gene regulation. We have recently shown that temperature-responsive miRNAs in Drosophila drive adaptation to different ambient temperatures on the transcriptome level. Moreover, we demonstrated that higher temperatures lead to a more efficient piRNA-dependent transposon silencing, possibly due to heat-induced unfolding of RNA secondary structures. In this commentary, we will dwell upon particular interesting aspects connected to our findings, hoping that our point of view may encourage other scientists to address some of the questions raised here. We will particularly focus on aspects related to climate-dependent transposon propagation in evolution and putative transgenerational epigenetic effects of altered small RNA transcriptomes. We further briefly indicate how temperature-responsive miRNAs may confound the interpretation of data obtained from experiments comprising heat-shock treatment which is a widely used technique not only in Drosophila genetics.